2015
DOI: 10.2174/1389202916666150817202217
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Origins of Osteoporosis

Abstract: Abstract:Osteoporosis is one of the most prevalent skeletal disorders and has enormous public health consequences due to the morbidity and mortality of the resulting fractures. This article discusses the developmental origins of osteoporosis and outlines some of the modifiable and non-modifiable risk factors in both intrauterine and postnatal life that contribute to the later onset of osteoporosis. Evidence for the effects of birth size and early growth in both preterm and term born infants are discussed and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 68 publications
(81 reference statements)
0
20
0
2
Order By: Relevance
“…In particular, ≤50% reduction in daily feed intake from early in gestation typically limits rabbit doe gestational weight gain and results in miscarriage, asymmetric IUGR, and fetal malformations, such as reduced bone ossification (Cappon, Fleeman, Chapin, & Hurtt, ; Clark et al, ; Flake, Villa, Adzick, & Harrison, ; López‐Tello et al, ; López‐Tello, Arias‐Álvarez, Jiménez‐Martínez, Barbero‐Fernández et al, ; López‐Tello, Arias‐Álvarez, Jimenez‐Martinez, Garcia‐Garciaet al, ; Matsuzawa, Nakata, Goto, & Tsushima, ; Petrere, ; Symeon et al, ). Offspring bone development is also impaired by malnutrition in other animal species, including rats that are exposed to a maternal low protein diet during gestation (Hanson & Gluckman, ; Hastings‐Roberts & Zeman, ; Wood, Stenson, & Embleton, ). A 70% reduction in feed intake (30% of control) during the last third of rabbit pregnancy also reduces maternal weight and leads to asymmetric IUGR (Eixarch et al, ; Illa et al, ; Matsuoka et al, ).…”
Section: Models Of Iugr and Fetal Programmingmentioning
confidence: 99%
“…In particular, ≤50% reduction in daily feed intake from early in gestation typically limits rabbit doe gestational weight gain and results in miscarriage, asymmetric IUGR, and fetal malformations, such as reduced bone ossification (Cappon, Fleeman, Chapin, & Hurtt, ; Clark et al, ; Flake, Villa, Adzick, & Harrison, ; López‐Tello et al, ; López‐Tello, Arias‐Álvarez, Jiménez‐Martínez, Barbero‐Fernández et al, ; López‐Tello, Arias‐Álvarez, Jimenez‐Martinez, Garcia‐Garciaet al, ; Matsuzawa, Nakata, Goto, & Tsushima, ; Petrere, ; Symeon et al, ). Offspring bone development is also impaired by malnutrition in other animal species, including rats that are exposed to a maternal low protein diet during gestation (Hanson & Gluckman, ; Hastings‐Roberts & Zeman, ; Wood, Stenson, & Embleton, ). A 70% reduction in feed intake (30% of control) during the last third of rabbit pregnancy also reduces maternal weight and leads to asymmetric IUGR (Eixarch et al, ; Illa et al, ; Matsuoka et al, ).…”
Section: Models Of Iugr and Fetal Programmingmentioning
confidence: 99%
“…Several research lines have since used the DOHaD framework to explain, for example, maternal obesity and foetal development [41], maternal hypertension and mental health in the offspring [42], susceptibility to developing cancer [43], obesity and type 2 diabetes [44] in later life. These models explaining extrinsic factors influencing human health at the intrauterine and later life phases have extended to osteoporosis [45][46][47][48][49][50]. For instance, developmental origins of osteoporosis have been considered based on bone mineral density (BMD) changes with premature births [45], and birth size and low birth weight effect on bone size [46,47].…”
Section: Modern Perspective Through Social Epidemiology and Epigenetimentioning
confidence: 99%
“…These models explaining extrinsic factors influencing human health at the intrauterine and later life phases have extended to osteoporosis [45][46][47][48][49][50]. For instance, developmental origins of osteoporosis have been considered based on bone mineral density (BMD) changes with premature births [45], and birth size and low birth weight effect on bone size [46,47]. It is now accepted that osteoporosis is a non-communicable disease [48][49][50], and should be studied using the life-course approach.…”
Section: Modern Perspective Through Social Epidemiology and Epigenetimentioning
confidence: 99%
“…Interestingly, a recent study reported that duration of breast feeding was positively associated with BMD at 17 years of age. 72 Our results raise the question whether colostral supplementation could be used to increase BMD in infants that receive formula milk or in pre-term infants who are more prone to a lower BMD than full-term infants 73 in order to achieve sustained BMD comparable to the levels found in adolescents that were breast-fed. A longer follow up of the development of BMD in our animals would have been necessary to answer this question.…”
Section: Discussionmentioning
confidence: 81%